Temperature dependence of the microscopic structure and density anomaly of the SPC/E and TIP4P-Ew water models. Molecular dynamics simulation results - Galicia-Andrés, E.; Dominguez, H.; Pizio, O. (Condensed Matter Physics, 2015)
We have investigated temperature trends of the microscopic structure of the SPC/E and TIP4P-Ew water models in terms of the pair distribution functions, coordination numbers, the average number of hydrogen bonds, the distribution of bonding states of a single molecule as well as the angular distribution of molecules by using the constant pressure molecular dynamics simulations. The evolution of the structure is put in correspondence with the dependence of water density on high temperatures down to the region of temperatures where the system becomes supercooled. It is shown that the fraction of molecules with three and four bonds determine the maximum density for both models. Moreover, the temperature dependence of the dielectric constant is obtained and analyzed.